PHYSICAL AND VERBAL VIOLENCE IN INDONESIAN FOLKTALES RETOLD IN CHILDREN’S BOOKS - Qanitah Masykuroh (Universitas Muhammadiyah Surakarta, 2016)
Folktales as a cultural expression can contain all aspects of human life including violence. As Indonesia comprises so many diverse cultures, the contextof violence, its degree and its nature, are also various. This study examines the forms of violence in Indonesian folktales, focusing on how physical and verbal violence are depicted in Indonesian folktales retold in children’s books that were published in ten years of post-reformasi period. Content analysis is used to scrutinize the forms of violence. The finding shows that physical and verbal violence in Indonesian folktales retold as children’s storybooks is prevalent. I argue that the diverse forms and nature of violence presented in children’s story books illuminate the connection between social and individual expressions of violence. This study provides a way to look at the structural and ideological function ofviolence in contemporary traditional folk literature.